2021
DOI: 10.1021/acsami.1c11315
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Al Doping on the Electrochemical Performance Improvement of the LiMn2O4 Cathode Material

Abstract: It is well known that the electrochemical performance of spinel LiMn2O4 can be improved by Al doping. Herein, combining X-ray diffraction, Raman spectroscopy, X-ray photoelectron spectroscopy, and spherical aberration-corrected scanning transmission electron microscopy (Cs-STEM) with in situ electron-beam (E-beam) irradiation techniques, the influence of Al doping on the structural evolution and stability improvement of the LiMn2O4 cathode material is revealed. It is revealed that an appropriate concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 51 publications
4
39
0
Order By: Relevance
“…The report of Peng Li et al has shown that doping of Al 3+ to a certain limit can reduce the capacity and increase the stability, 29 and the reports of C.Peng et al and Xu et al have shown that the capacity decays if the Al 3+ ratio increases. 36,37 The same behavior is observed in our materials.…”
Section: Electrochemical Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…The report of Peng Li et al has shown that doping of Al 3+ to a certain limit can reduce the capacity and increase the stability, 29 and the reports of C.Peng et al and Xu et al have shown that the capacity decays if the Al 3+ ratio increases. 36,37 The same behavior is observed in our materials.…”
Section: Electrochemical Characterizationsupporting
confidence: 88%
“…Though, the presence of Al in the structure helps in stability rather than improving the discharge capacity. 31,36,37,57 EIS studies were performed with two-electrode system for the fresh cells to know the interface resistance and kinetics of the Li + insertion/exertion mechanism. The obtained data have been fitted with the equivalent circuit, which is provided in the inset of Figure 5b, where R1 represents the Ohmic resistance due to the electrochemical system (R s ), R 2 represents the resistance of the SEI (R SEI ), R 3 represents the chargetransfer resistance (R ct ), CPE represents the constant phase element (Q), and W is the Warburg diffusion impedance (W).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…LiZn x Mn 2– x O 4 (0 ≤ x ≤ 0.1) octahedron particles are prepared by a hydrothermal treatment and calcination process, as reported in our previous studies. First, to obtain Mn 3 O 4 nanoparticles with better reaction activity and smaller particles, commercially purchased Mn 3 O 4 powders (1.0 g) were dispersed into a NaOH aqueous solution (30 mL, 5 mol dm –3 ) with magnetic stirring for 1 h. Afterward, the dispersion was transferred to a Teflon-lined stainless-steel autoclave (50 mL) and heated at 205 °C for 4 days in an oven. The final precipitated products were collected and washed repeatedly with deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, researchers have carried out a wide range of studies to mitigate Mn dissolution, including modulation of particle morphology, changing electrolyte components, coating, , and doping. , Since doping can affect the intrinsic stability of the material by regulating the interaction between atoms, we chose to study the effects of (surface) doping on Mn dissolution of the LMO cathode. Taking the 3.5+ nominal valence of Mn ions in the LMO cathode as the demarcation, the dopants that have been studied can be divided into two categories: (1) elements with 2+/3+ nominal valence such as Mg, Al, , Cu, Zn, and so forth. Researchers believe that these elements can reduce the proportion of Mn 3+ in the LMO cathode, thus reducing the deterioration of the LMO cathode properties due to the disproportionation reaction and the John–Teller effect. , (2) Elements with nominal valence higher than 3+ such as Ti, V, Cr, Nb, , and so forth.…”
Section: Introductionmentioning
confidence: 99%